Isolation and Molecular Identification of Entomopathogenic Nematodes (Steinernema and Heterorhabditis) from East Java and Bali - Chaerani, Chaerani; Prabowo, Heri; Indrayani, I G.A.A (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
Entomopathogenic nematode of the families Steinernematidae and Heterorhabditidae is one of the best biological control agents of insect pests. Native isolates maybe more efficacious in controlling insect pests than imported ones because they have adapted to local environment. This study aimed to isolate and identify both nematode families from East Java and Baliusing DNA analysis. Sixty eight soil samples obtained from sandy soils in 16 sites of coastal regions and agricultural fields were tested for the presence of nematodes by baiting method with mealworm larvae (Tenebrio molitor). Five Heterorhabditis and two Steinernema were recovered from 7 soil samples (10% of total samples) of 7 sites (44% of total sites). Sequence analysis ofinternal transcribed spacer (ITS) 1 and 2 regions of ribosomal DNA revealed that all Heterorhabditis belonged to indica species, with 99â€“100% nucleotide sequence similarities to published sequences. One of the Steinernema isolates had short infective juvenile body length (360 Î¼m to 547 Î¼m) and shared 99% nucleotide similarity to that of S. huense, a member of â€œcarpocapsaeâ€ group. The other Steinernema isolate (DKS1) showed longer infective juvenile body length (from 548 Î¼m to 762 Î¼m) and shared 95% nucleotide similarity to the sequence of S. pakistanense, which belongs to â€œbicornutumâ€ group. More detailed studies with respect to morphology are required for species confirmation of DKS1 isolate. Further exploration todiverse habitat will likely to result in more previously unrecorded entomopathogenic nematode species in Indonesia.